South Pole ice core (SPC14) discrete methane data - Epifanio, Jenna; Brook, Edward J; Buizert, Christo; Severinghaus, Jeffrey; Kreutz, Karl; Aydin, Murat; Edwards, Jon S.; Sowers, Todd A.; Kahle, Emma; Steig, Eric J.; Winski, Dominic A.; Osterberg, Erich; et al. (U.S. Antarctic Program (USAP) Data Center, 2020)
We present the methane (CH4) concentration data for the South Pole ice core (SPC14). CH4 concentrations were measured jointly at Oregon State University and Pennsylvania State University. All depths are in meters below the surface. Methane data have been corrected for blank offsets, solubility, and gravitational fractionation. All ages are in years before 1950 C.E. on the SP19 gas chronology.